Hydrogeological investigations of the resurgence Šumetac on the river Kolpa and its tributary area - Rogelj, Janez; Novak, Dušan (Geologija, 1992)
Within the frame of hydrogeological investigations for the substitution of water supply plant Dolski potok dye tests have been made on two of the sinking brooks. The brooks sinking at the Southern borderland of Šibje hill between Mozelj and Knežja Lipa have been color traced. The dyed water reappeared in the resurgence of Šumetac on the river Kolpa after eleven resp. three days.